(untitled) (Mongolian Journal of Applied Linguistics, 2025)
The article deals with the formation of professional words in the transport sector and examines the methods in Mongolian language. Professional words in the transport sector particularly in road transport are formed through phonological processes and analogy, as well as through the use of jargon and idiomatic expressions. Professional words serve an intermediary function between terminology and literary language vocabulary, possessing transitional characteristics; therefore, they have full potential to develop into formal terms. Idiomatic specialized expressions that convey concepts and notions through their defining features, similar to terminological phrases, are frequently encountered. In addition, jargon is considered part of professional words and plays an important role in making speech more vivid and expressive, as well as in conveying linguistic signals concisely and precisely. There through professional language consists of professional words, professional jargon, and terminology. Тээврийн салбарын мэргэжлийн үг үүсэх аргын тухай Хураангуй: Энэхүү өгүүлэлд тээврийн салбараар тоймлон, монгол хэлний мэргэжлийн үг үүсэх арга, зүй тогтлыг авч үзэв. Тээврийн салбар, тэр дундаа зам тээврийн салбарын мэргэжлийн үгс авиа зүйн болон адилтгалын аргаар, мөн этгээд үг, хэлц үгийн хэв маягаар үүсэж байна. Мэргэжлийн үг нь нэр томьёо, утга зохиолын хэлний үг хоёрын дунд зуучийн үүрэгтэй, завсрын шинжтэй тул нэр томьёо оноох бүрэн боломжтой. Тухайн ойлголт, ухагдахууныг шинж чанараар нь илэрхийлсэн хэлц нэр томьёотой адил хэлц мэргэжлийн үг олонтоо тохиолдож байна. Мөн этгээд үг хэллэг нь мэргэжлийн үгэнд хамаарах бөгөөд хэл яриаг хөхиүн хөгжүүн болгох, хэлний дохиог товч, оновчтой цомхон илэрхийлэх зэрэг ач холбогдолтой юм. Ийнхүү мэргэжлийн үг, мэргэжлийн этгээд үг, нэр томьёо нь мэргэжлийн хэлийг бүрдүүлнэ. Түлхүүр үг: мэргэжлийн хэл, мэргэжлийн үг, нэр томьёо, адилтгалын арга, хэлц үг, этгээд үг